2021
DOI: 10.5860/crl.82.3.300
|View full text |Cite
|
Sign up to set email alerts
|

The Contested One-Shot: Deconstructing Power Structures to Imagine New Futures

Abstract: For so long the one-shot has been the dominating force of how we engage in library instruction. There is a lot of meaning and debate saturated in this faux-innocuous activity, yet there is not always consensus as to how we define a one-shot. Is it doing a library "spiel" to demo a database, present the library website, or give a tour? Is it visiting a class once without an explicit connection to an assignment? Is it even embedding a learning object in a class without assessment feedback or other interaction? T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…The ability to have agency over one's teaching approach sometimes requires establishing and upholding boundaries with one-shot requests, but not all librarians have the support to advocate and push back, depending on their positionality (Pagowsky, 2021;Chesley & Anantachai, 2018). One interviewee reported that her department tried to question teaching one-shots that did not seem to be aligned with the goals of her library unit; but, when the library administration found out, they were unhappy and opposed the change, seeing it as a diminishing of services.…”
Section: Empowerment/disempowermentmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to have agency over one's teaching approach sometimes requires establishing and upholding boundaries with one-shot requests, but not all librarians have the support to advocate and push back, depending on their positionality (Pagowsky, 2021;Chesley & Anantachai, 2018). One interviewee reported that her department tried to question teaching one-shots that did not seem to be aligned with the goals of her library unit; but, when the library administration found out, they were unhappy and opposed the change, seeing it as a diminishing of services.…”
Section: Empowerment/disempowermentmentioning
confidence: 99%
“…This poignant quote, written in an email inviting fellow authors to collaborate on this article, kicked off a series of conversations exploring how and why one-shots became a standard practice in the sphere of academic library instruction. Nicole Pagowsky's editorial (2021) about deconstructing power structures that inform "the contested one-shot" inspired this group of authors to reflect back on our own understanding and perspective of the one-shot model and act upon Pagowsky's call "to expand our pedagogical imagination through questioning what appear to be common-sense practices in order to create better systems and structures" (Pagowsky, 2021). Many instruction librarians start their careers teaching information literacy sessions using primarily one-shots.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The one-shot is the primary information literacy format at myriad institutions, including mine. Librarians are deeply aware of the limitations of the one-shot approach (Julien, Gross, and Latham 2018;Pagowsky 2021): one class session is insufficient to achieve measurable, lasting learning; it assumes a banking model of education; and it positions librarians as service providers when they are also teachers (Pagowsky 2021). As a result, academic librarians hope to replace the oneshot model with a more effective approach that integrates and scaffolds information literacy throughout the curriculum.…”
Section: Addressing the Limitations Of One-shot Instructionmentioning
confidence: 99%
“…3 The one-shot-a one-time-only information literacy or research workshop that takes place within the context of faculty-led courses-is seen as a consolation prize: ineffective, exhausting, tacked on, and demoralizing. 4 However, there are one-shot classes or workshops that leave us, as librarians, feeling connected to students and faculty, deeply moved by the learning that has happened in the last hour or two (and in the hours of planning before the class even occurs). Conversely, we may have taught semester-long courses that leave us drained, questioning the purpose of the hours spent in the classroom.…”
Section: Introductionmentioning
confidence: 99%